57.9k views
5 votes
Simplify the given expression below 4/3-2i

a. 4/13
b. 16/13
c. 12+8i/13
d. 12-8i/13

1 Answer

6 votes

The correct answer is
(4)/(3-2i)=(12)/(13)+i(8)/(13)

Steps:


\mathrm{Multiply\:by\:the\:conjugate}\:(3+2i)/(3+2i), =(4\left(3+2i\right))/(\left(3-2i\right)\left(3+2i\right))


\left(3-2i\right)\left(3+2i\right)=13, =(4\left(3+2i\right))/(13)


\mathrm{Rewrite\:}(4\left(3+2i\right))/(13)\mathrm{\:in\:standard\:complex\:form:\:}(12)/(13)+(8)/(13)i


=(12)/(13)+(8)/(13)i

User JNWHH
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.